2018
DOI: 10.1063/1.5023386
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguring droplet interface bilayer networks through sacrificial membranes

Abstract: The droplet interface bilayer platform allows for the fabrication of stimuli-responsive microfluidic materials, using phospholipids as an organic surfactant in water-in-oil mixtures. In this approach, lipid-coated droplets are adhered together in arranged networks, forming lipid bilayer membranes with embedded transporters and establishing selective exchange pathways between neighboring aqueous subcompartments. The resulting material is a biologically inspired droplet-based material that exhibits emergent prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…3 b lower panel). Previous works have shown that solvents that produce more stable bilayers result in higher energy of adhesions 8 , 17 and will require more force to separate. The use of the 1:1 hexadecane:silicone oil AR20 solvent in DIBs has been traditionally preferred since it reduces gravitational influences on the droplets and allows for the formation of stable networks 15 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 b lower panel). Previous works have shown that solvents that produce more stable bilayers result in higher energy of adhesions 8 , 17 and will require more force to separate. The use of the 1:1 hexadecane:silicone oil AR20 solvent in DIBs has been traditionally preferred since it reduces gravitational influences on the droplets and allows for the formation of stable networks 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by how cellular tissues structurally adapt, we will explore how magnetically driven shape shifting capabilities can be implemented in materials constructed using the droplet interface bilayer (DIB) technique, a popular technique for assembling lipid membranes that may be used to recreate cellular phenomena 6 . Building on previous works 7 , 8 , ferrofluids will be integrated into our DIB-systems and used to reconfigure neighboring lipid membranes through magnetic forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4(b), a large flexoelectric electric field will exist in the vicinity of the cracks of the hydroxyapatite. The bio-membrane flexoelectricity was recently studied by using the droplet interface bilayer technology (DIB) [62][63][64][65]. The principle of DIB in this scenario, as shown in Fig.…”
Section: Flexoelectricity In Biological Materialsmentioning
confidence: 99%
“…Ionic amplifiers with ionic output could also enable local delivery of molecules used, for example, in controlling local polymerization 16 , as suggested in an earlier work 10 ; more generally, delivery of different molecules at different parts of ionic circuits would lead to spatially and temporally complex patterns of chemical reactions, and emergent phenomena 6,[17][18][19] . In addition, if ionic transistors are based on channels in a membrane, they could be used in setups that mimic biological systems and enhance transmembrane ionic flow [20][21][22][23][24][25][26] .…”
mentioning
confidence: 99%